2018
DOI: 10.1111/jre.12557
|View full text |Cite
|
Sign up to set email alerts
|

A novel, cell‐permeable, collagen‐based membrane promotes fibroblast migration

Abstract: Incorporation of FN into IGF-I-loaded collagen+Vicryl membranes reduced IGF release from collagen and increased the migration of human gingival fibroblasts. The new membrane may promote healing and reformation of the dentogingival junction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…The application of CPC in concert with collagen membranes leads to enhanced alveolar bone growth compared with controls, indicating that the inclusion of CPC with collagen membranes may simplify wound closure. We also found a reduction of pocket depth (p < 0.05) due to the inclusion of IGF-1 in the membranes, which is consistent with a previous in vitro study that described the inclusion of IGF-1 in collagen membranes and the effect of this cytokine in promoting cell migration (Sadeghi et al, 2018). Our use of Yorkshire pigs as a large animal model for screening of different treatments indicates that pigs may be used in early stage studies to examine promotion of reattachment of periodontal tissues to the denuded root surface and in the restoration of lost alveolar bone.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The application of CPC in concert with collagen membranes leads to enhanced alveolar bone growth compared with controls, indicating that the inclusion of CPC with collagen membranes may simplify wound closure. We also found a reduction of pocket depth (p < 0.05) due to the inclusion of IGF-1 in the membranes, which is consistent with a previous in vitro study that described the inclusion of IGF-1 in collagen membranes and the effect of this cytokine in promoting cell migration (Sadeghi et al, 2018). Our use of Yorkshire pigs as a large animal model for screening of different treatments indicates that pigs may be used in early stage studies to examine promotion of reattachment of periodontal tissues to the denuded root surface and in the restoration of lost alveolar bone.…”
Section: Discussionsupporting
confidence: 92%
“…Membranes for implantation into periodontal tissues were prepared in a similar manner as described (Sadeghi et al, 2018). Briefly, 3 mg/ mL porcine atelo collagen type I (Felxicol, Advanced Biomatrix, Carlsbad, CA) was combined with 10 μg/mL FN (final concentration; Sigma) or rh-AMTN (final concentration 530 μg/mL).…”
Section: Preparation Of Membranesmentioning
confidence: 99%
“…The average cell migration index is small for all the study groups. This is not specific to CNT/GC hydrogel, as it has been previously reported that in normal in vitro conditions only a few percents of fibroblasts migrate through chemotactic mechanisms 40,43 . The cell concentration that we used in the chemoattractant-induced cell migration experiment was less than 7 million cells/ml, which is drastically lower than that of a native vocal fold tissue (66~300 million cells/ml) 44,45 .…”
Section: Discussionmentioning
confidence: 76%
“…The fibroblasts were passed, counted, and encapsulated in vials of hydrogels. Since the overall migration rate was predicted to be small 40 , we aimed for an initial population of 1~1.4 million fibroblasts in each insert to obtain enough migrated cells for comparison. Prior to gelation, 200 μl of the hydrogel was transferred from the vials to porous www.nature.com/scientificreports www.nature.com/scientificreports/ inserts.…”
Section: Chemoattractant-induced Cell Migration Cell Migration In Comentioning
confidence: 99%
“…Despite this, there were numerous other studies that employed even more complex collagen matrices than a simple coating, confirming the positive effect of this structural protein on the growth, vitality, and migration of fibroblasts [ 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 96%